More than Collectors: Exploring Theorists', Hobbyists' and Everyday Players' Rhetoric in Adult Play With Character Toys - Katriina Heljakka (Sage Publications, 2022)
The article aims to present, analyze, and discuss the attitudes of the three groups of adults—theorists, hobbyists and “everyday players”—toward play(ful) behavior and activities in relation to character toys. The rhetoric of play theorists is mirrored against the rhetoric of organized players (hobbyists) and (nonorganized) everyday players through in-depth interviews and participatory observation. Questions guiding the exploratory path this article takes include the following: First, what has led to the dominant ideas of the toy as a collectable item and of adult toy consumers as toy collectors? Second, why is the manipulation of toys that happens at adult age considered hobbying and not playing? The results of the analysis indicate that the uses of toys at adult age represent more complex and multifaceted actions and relationships to play than the terms “collecting” and “hobbying” imply.